Increased synthesis of pro-inflammatory cytokines in C9ORF72 patients. Issue 7 (2nd October 2021) - Pinilla, Gabriel; Kumar, Anupama; Floaters, Mary Kay; Pardo, Carlos A.; Rothstein, Jeffrey; Ilieva, Hristelina
Abstract: C9ORF72 hexanucleotide expansion is the most common genetic cause of familial amyotrophic lateral sclerosis (ALS)/fronto-temporal dementia (FTD) disease spectrum. Even though three major mechanisms of disease pathogenesis have been proposed, we lack detailed understanding of the factors that influence disease onset and progression. We sought to characterize cerebrospinal fluid and sera of C9ORF72 patients via a multiplex assay of 41 chemokines and cytokines in comparison to neurological controls and sporadic ALS patients. We found an increase in synthesis of pro-inflammatory chemokines and cytokines in disease samples and particularly in C9ORF72 patients in comparison to controls. We provide evidence that a CSF pro-inflammatory signature is a feature of C9ORF72–mediated disease.